Experimental evaluation of carbonated brine-limestone interactions under reservoir conditions-emphasis on the effect of core scale heterogeneities - Khather, M.; Saeedi, Ali; Rezaee, M. Reza; Noble, R. (Elsevier, 2018)
CO 2 injection into deep geological structures is very often accompanied by chemical interactions between the host rock and injected fluids and/or the in-situ created solute (i.e. carbonated brine). In fact, the in-situ reactions are considered one way through which the injected CO 2 may be trapped for perpetuity. Depending on the nature and mineralogy of the host rock formation, such reactions may eventually result in a degree of change in the petrophysical properties of the rock. Carbonate formations, due to the presence of highly reactive minerals in their composition, are expected to be more prone to such changes than their sandstone counterparts. This manuscript presents the results of an experimental study conducted to evaluate possible changes in the petrophysical properties of five heterogeneous limestone samples (calcite concentration > 91 wt%). The study includes five reservoir condition core-flood experiments (i.e. one per each rock sample) complemented by other laboratory measurements/analyses including porosity-permeability measurements, X-ray CT (X-ray Computed Tomography) and SEM (Scanning Electron Microscopy) imaging. The results show a significant increase in the post-flood permeability of 80% of the samples caused by the dissolution and removal of carbonate minerals. The X-ray CT images reveal signs of significant mineral dissolution and establishment of flow paths through the initial larger pores in the samples leading, eventually, to the formation of wormhole features along the length of the samples. On the contrary, reduction in permeability is observed in one sample which was a relatively long (15.8 cm) composite sample consisting of two core segments placed one after the other in series. The other four samples were shorter with a nominal length of 6.4 cm. This reduction in permeability is observed predominantly in the outlet segment. This change is thought to have been primarily caused by possible migration of carbonate fines released by mineral dissolution in the inlet plug of the long composite core and to a lesser extent by the precipitation of minerals dissolved and transported from the inlet plug. This hypothesis finds further support in the pre- and post-flood dry weight measurements as well as a post-flood SEM image of the plug which reveals signs of fines migration and mineral precipitation. Slight reductions in the porosity and pore sizes are observed in most of the samples. This is likely to have been caused by the combined effect of fines migration, possible mineral precipitation and physical compaction mechanisms. Mechanical compaction is further evident from the reductions in the physical dimensions of the samples. Overall, the results obtained show that the nature and degree of any change in the petrophysical properties of the rock samples vary to some degree from one sample to the next. This variation is found to depend on the significance and degree of dominance of the three mechanisms of mineral dissolution, mineral precipitation and mechanical compaction if they occur during the flooding process. The migration of carbonate fines also seems to be an important factor in shaping the post-flood sample properties. The presence of any initial core scale heterogeneity in the pre-flood samples is also believed to be a critical factor controlling the eventual outcome.